An Error Analysis on the Use of Simple Past Tense - Abdullah Syukur; Ardhy Supraba (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2022)
The objectives of this study are (1) to identify and classify the errors of the second semester students of Informatic Study Program Cokroaminoto Palopo University in using simple past tense, (2) to describe the frequency occurrence of the errors. The instrument used was a test on English simple past tense. The population of the study was the second semester students of Informatic Study Program Cokroaminoto Palopo University. The sample consisted of 50 students. Students errors identified in this study were categories into three types, namely, errors of omission, errors of addition and errors of misformation. The result of the analysis shows that there were in all, 1234 errors among 50 students. The types of errors among the students in constructing and using English simple past tense consisted of 68 (5%) errors of omission, 95 (8%) errors of addition and 1071 (87%) errors of misformation. From the highest to the lowest, the errors were: misformation, addition, and omission. The result of further analysis shows that the students seemingly have problems in each category omission, addition and misformation. The average number of errors made of all the students was 46%. From the percentage, it can be concluded that the students’ mastery in using English simple past tense was poor. It is hoped that the finding of the present study will be useful for the teaching of English, especially the teaching of English simple past tense.